Overcoming History through International Organizations - Historical Roots of EU Support and Euroscepticism - Kai Gehring (Center for Economic Studies and ifo Institute (CESifo), 2019)
There is little causal evidence about deep-rooted sources of support for shifting power from nation-states to international organizations. Focusing on the European Union, this paper develops the hypothesis that citizens appreciate the role of international organizations in constraining member-states the more, the more negatively their region was historically affected by the actions of nation-states. For identification, I use the historically homogeneous regions of Alsace and Lorraine in France as a natural experiment. A municipal level geographical regression discontinuity design documents that more negative exposure led to persistently higher EU support in three important referenda and less success of Eurosceptic parties in parliamentary elections. This effect is not driven by linguistic differences, migration, socio-economic factors or public good provision, but linked to a stronger European identity. This stronger identity is neither explained by perceived economic benefits, nor comes at the expense of a weaker national or regional identity.
Keywords: D70; F50; H70; N24; 330; international organizations; nation-states; repression; persistence; group identity; European Union support; Euroscepticism; European identity